2023
DOI: 10.1155/2023/7482546
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Mitochondria Attenuate 5-FU-Induced Injury to Bone-Associated Mesenchymal Stem Cells

Abstract: Background. Myelosuppression is a common condition during chemotherapy. Bone-associated mesenchymal stem cells (BA-MSCs) play an essential role in the composition of the hematopoietic microenvironment and support hematopoietic activity. However, chemotherapy-induced damage to BA-MSCs is rarely studied. Recent studies have shown that platelets promote the wound-healing capability of MSCs by mitochondrial transfer. Therefore, this study is aimed at investigating the chemotherapy-induced damage to BA-MSCs and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…However, under certain types of stress, including nutritional nutrient starvation and oxidative stress, cells may adaptively elongate mitochondria through mitochondrial fusion to dilute damaged mitochondrial proteins and enhance energetic efficiency [ 61 , 62 ]. Several other studies have also observed mitochondrial elongation, along with active mitochondrial fission and fusion, which were associated with the maintenance of mitochondrial health and resistance to dysfunction [ 63 , 64 ]. Therefore, we speculated that mitochondrial elongation corresponded to an event of fusion-dominated mitochondrial dynamic changes in ESCs, adapting to the energy shortages caused by TGF-β1 mediated mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, under certain types of stress, including nutritional nutrient starvation and oxidative stress, cells may adaptively elongate mitochondria through mitochondrial fusion to dilute damaged mitochondrial proteins and enhance energetic efficiency [ 61 , 62 ]. Several other studies have also observed mitochondrial elongation, along with active mitochondrial fission and fusion, which were associated with the maintenance of mitochondrial health and resistance to dysfunction [ 63 , 64 ]. Therefore, we speculated that mitochondrial elongation corresponded to an event of fusion-dominated mitochondrial dynamic changes in ESCs, adapting to the energy shortages caused by TGF-β1 mediated mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%